Metabolic syndrome and physical inactivity in adults: a case-control study (Research, Society and Development, 2022)
The aim of the study was to evaluate the association of metabolic syndrome with physical inactivity. A case-control study was carried out, nested in a population-based cross-sectional. Adults aged 20 to 59 years old, of both sexes, residing in Dourados-MS constituted a sample. Cases involved 149 with three or more criteria: 1) blood pressure ≥ 130 x 85 mmHg or using antihypertensive drugs; 2) waist awareness ≥ 90 cm (men and ≥ 80 cm (women); 3) fasting blood glucose ≥ 100 mg/dl or using hypoglycemic drugs; 4) HDL < 40 mg/dl (men) and < 50 mg/dl (women); and 5) triglycerides ≥ 150 mg/dl or using lipid-lowering drugs. Controls were drawn among subjects who did not have metabolic syndrome (n = 152). Data analysis was performed using the following tests: T-Test, Fisher's Exact, Chi-Square and Unconditional Logistic Regression. The inactive and overweight individuals were 11 times more likely to have metabolic syndrome than active and of normal weight. Elderly mentioned four times more metabolic syndrome than younger; men reported twice as many syndrome than women; and those with less schooling, twice as many syndrome as more schooling. The study demonstrates a great need to expand public health policies that encourage the practice of physical activity, as well as improve the quality of the population's diet, in order to mitigate the risk of developing metabolic syndrome.